Sportsman’s hernia - Vagholkar, Ketan; Garima, Shivangi; Kripalani, Yash; Chandrashekhar, Shantanu; Vagholkar, Suvarna (International Surgery Journal, 2019)
Sportsman’s hernia is a complex entity with injuries occurring at different levels in the groin region. Each damaged anatomical structure gives rise to a different set of symptoms and signs making the diagnosis difficult. The apprehension of a hernia is foremost in the mind of the surgeon. Absence of a hernia sac adds to the confusion. Hence awareness of this condition is essential for the general surgeon to avoid misdiagnosis.